Information security education : information security in action : 13th IFIP WG 11.8 World Conference, WISE 13, Maribor, Slovenia, September 21-23, 2020, Proceedings /: information security in action : 13th IFIP WG 11.8 World Conference, WISE 13, Maribor, Slovenia, September 21-23, 2020, Proceedings. ([2020]) - Unknown
No abstract available